1993
DOI: 10.1002/cne.903300103
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity and selectivity of the degeneration of cholinergic neurons in the basal forebrain of patients with Alzheimer's disease

Abstract: Cholinergic neurons were studied by immunohistochemistry, with an antiserum against choline acetyltransferase (ChAT), in the basal forebrain (Ch1 to Ch4) of four patients with Alzheimer's disease (AD) and four control subjects. ChAT-positive cell bodies were mapped and counted in Ch1 (medial septal nucleus), Ch2 (vertical nucleus of the diagonal band), Ch3 (horizontal nucleus of the diagonal band) and Ch4 (nucleus basalis of Meynert). Compared to controls, the number of cholinergic neurons in AD patients was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
115
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(124 citation statements)
references
References 67 publications
7
115
1
1
Order By: Relevance
“…3A in Mufson et al, 1989). The cell group designated as Ch3 in our paper represents a transitory area between the septum-diagonal band complex and the more caudal cell groups of the magnocellular basal forebrain system and may correspond to be part of the anteromedial Ch4 group in some publications (Mesulam et al, 1983;Lehericy et al 1993;Gilmor et al, 1999). We, and others, noted that a separation of the anterior Ch4 group into medial and lateral sectors by a vascular structure, as proposed by Mesulam and his coworkers, is ambiguous due to the variation of the vessels (Halliday et al, 1993;Swaab, 2003).…”
Section: Organization Of the Human Magnocellular Basal Forebrain Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…3A in Mufson et al, 1989). The cell group designated as Ch3 in our paper represents a transitory area between the septum-diagonal band complex and the more caudal cell groups of the magnocellular basal forebrain system and may correspond to be part of the anteromedial Ch4 group in some publications (Mesulam et al, 1983;Lehericy et al 1993;Gilmor et al, 1999). We, and others, noted that a separation of the anterior Ch4 group into medial and lateral sectors by a vascular structure, as proposed by Mesulam and his coworkers, is ambiguous due to the variation of the vessels (Halliday et al, 1993;Swaab, 2003).…”
Section: Organization Of the Human Magnocellular Basal Forebrain Systemmentioning
confidence: 99%
“…Severe involvement of the magnocellular basal complex has been found in Alzheimer's disease, where various studies reported cell loss up to 90% (Whitehouse et al, 1981;Vogels et al, 1990;Lehericy et al, 1993;Cullen and Halliday, 1998). Estimations of the neuronal loss of basal nucleus of Meynert during normal aging also vary greatly from 23% to 50% to no neuronal loss at all (Whitehouse et al, 1981;Chui et al, 1984;De Lacalle et al, 1991).…”
Section: Age and Disease-related Changes In The Magnocellular Basal Cmentioning
confidence: 99%
“…A possible common candidate accounting for the loss of synchronization could be the profound loss of cortical cholinergic projections from the basal nucleus of Meynert, since this is a characteristic of AD, DLB and PDD (Braak et al 2003;Londos et al 2002;Lippa et al 1999;Cullen and Halliday 1998;Lehericy et al 1993;Vogels et al 1990;Candy et al 1983). Involvement of the cholinergic system is supported by an animal study, in which lesioning of the cholinergic system resulted in a reduction of long distance intrahemispheric as well as interhemispheric coherence (Holschneider et al 1999).…”
Section: Pddmentioning
confidence: 99%
“…Initial studies of the basal forebrain in DAT suggested that decrements in cortical ChAT were the result of frank loss of nucleus basalis cholinergic magnocellular neurons (72,73). However, more detailed analyses revealed that cholinergic neurons were generally shrunken and dysfunctional, but not dead, except in late-stage DAT (74)(75)(76)(77)(78)(79). These neuronal phenotypic changes without frank neuronal degeneration also occur early in cognitive decline (80).…”
Section: Plasmalogens and Dat Neurodegenerationmentioning
confidence: 99%